University brand as an employer: demystifying employee attraction and retention - Mohammad Yameen; Shubhangi Bharadwaj; Izhar Ahmad (Vilakshan (XIMB Journal of Management))
Purpose – This study aims to unveil the determinants of employer branding (EB) that attracts and retains the employees working in the Indian higher education sector using the factor-analytic approach. Design/methodology/approach – The study is cross-sectional, and the data were collected from 141 employees working in the higher education sector. Exploratory factor analysis and independent t-test were deployed to analyze the data. Findings – The results of independent samples t-test explicate that perception of male and female university employees pertaining to EB factors of employee attraction (EA) and employee retention (ER) is congruent. Further, the perception of employees in public and private universities on EB factor is similar for ER and non-similar for EA. Originality/value – The present research is an effort to unveil the employee attraction and retention factors that play a vital role in showcasing an employer as a great place to work in the Indian higher education sector.